Analysis of the Impact of Parking on Traffic Performance on the Roads Around the Cisaat Market - Eka Gadara; Utamy Sukmayu Saputri; Ardin Rozadi; Muhammad Hidayat; Zalavsky Nikolay Ivanovich (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2021)
The Cisaat Sukamanah highway is one of the arterial road segments that pass through Sukamanah Village, Cisaat District, Sukabumi Regency, West Java and is the main road connecting Cisaat Regency with Sukabumi City. This road belongs to the category of arterial road, for urban road conditions it is designed with a speed of 60 km/hour. In addition, on arterial roads, traffic should not be disturbed by local activities. The purpose of this study is to determine the performance of the Cisaat Sukamanah Highway, especially in front of the Cisaat Baru Market, in its current (existing) condition, to estimate the conditions on the Cisaat Highway. -12.00 wib with a total of 995.1 smp/hour vehicles. And the average speed is 192.3. For the highest side friction incident occurred on Monday at 06.45-07.45 with 453.3 hourly weighted events. Overall, the performance of the Cisaat Sukamanah highway is B. The highest accumulation results in the on street parking area of Jalan Pasar Baru on Sunday, March 21, 2021 for motorcycles were 681 vehicles occurring at 16.00-17.00 WIB and car vehicles were 230 vehicles occurring at 13.00-14.00. The results of observations in this study indicate that the overall parking volume on Sundays for motorbikes is 4709 and for cars is 2210. And the parking turnover rate obtained from the calculation results shows that the use of parking spaces, the parking turnover rate (Parking Turn Over) for motorbikes is 8, 4 vehicles/space and 17 vehicles/space for 11 hours of observation. And the average percentage of the parking index using motorcycle and car parking spaces on Sundays exceeds 100%. Thus, it can be concluded that the parking area is not efficient in accommodating parking vehicles.